2020
DOI: 10.1186/s12872-020-01721-9
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological outcome after cardiac arrest: a prospective case control sub-study of the Targeted hypothermia versus targeted normothermia after out-of-hospital cardiac arrest trial (TTM2)

Abstract: Background This study is designed to provide detailed knowledge on cognitive impairment after out-of-hospital cardiac arrest (OHCA) and its relation to associated factors, and to validate the neurocognitive screening of the Targeted Hypothermia versus Targeted Normothermia after Out-of-Hospital Cardiac Arrest trial (TTM2-trial), assessing effectiveness of targeted temperature management after OHCA. Methods This longitudinal multi-cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 60 publications
2
10
0
1
Order By: Relevance
“…In the present study, we used the Mini MoCA test and AD-8, which were developed and validated for patients with Alzheimer’s disease. The occurrence of cognitive impairment (23.7%) and emotional disorders (28.9%) 6 months after a cardiac arrest is consistent with previous studies 4 , 5 , 29 . Based on HADS scale, the prevalence of anxiety and depression among OHCA survivors are previously reported to be about 20–30% 28 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the present study, we used the Mini MoCA test and AD-8, which were developed and validated for patients with Alzheimer’s disease. The occurrence of cognitive impairment (23.7%) and emotional disorders (28.9%) 6 months after a cardiac arrest is consistent with previous studies 4 , 5 , 29 . Based on HADS scale, the prevalence of anxiety and depression among OHCA survivors are previously reported to be about 20–30% 28 .…”
Section: Discussionsupporting
confidence: 91%
“…Approximately 6–11% of patients who experience an out-of-hospital cardiac arrest (OHCA) are discharged with good neurological outcomes, as defined by a Cerebral Performance Category (CPC) score ≤ 2 or Modified Rankin Scale score ≤ 3 1 , 2 . However, the consequences of cardiac arrest, even in cases of favorable neurological outcomes, can limit patients’ daily activities, psychological conditions, and quality of life (QoL) 3 , 4 . Several studies have reported that OHCA survivors may be cognitively impaired, predominantly regarding memory and executive functions, and emotional problems, including anxiety and depression, during long-term follow-up 5 7 .…”
Section: Introductionmentioning
confidence: 99%
“…This predefined case–control sub-study is a part of the international, multicenter Targeted Hypothermia versus Targeted Normothermia after Out-of-Hospital Cardiac Arrest (TTM2) trial [ 12 , 13 ], in which 8 of 61 TTM2-sites participated. The study protocol has been published [ 14 ] and the study registered at ClinicalTrials.gov, NCT03543371.…”
Section: Methodsmentioning
confidence: 99%
“… 16 Patients were treated according to the TTM2-trial protocols regarding inclusion and exclusion criteria, randomisation, clinical management, neurological prognostication, decisions on withdrawal of life-sustaining therapy (WLST) and follow-up. 20 , 22 , 23 …”
Section: Methodsmentioning
confidence: 99%